STEM leaders promoting resilience within equity-centered K-12 STEM education organizations - Marshall, Stefanie L.; Galey-Horn, Sarah (Frontiers in Education, 2024)
Equity-centered policies and practices are instrumental to the design of an infrastructure that yields equitable STEM learning experiences. The enactment of policies and management structures is ultimately decided by those in school and district leadership positions (e.g., principals, superintendents, and central office personnel) (NASEM, 2021). Although various federal, state, local, and industry initiatives have promoted STEM education in schools, sustaining STEM programming long-term is challenging. This study examines storytelling's role in supporting organizational resilience for equitable STEM instruction by schools and districts. Within K-12 organizations, some practices may be perceived as mundane, but storytelling supports transformation toward achieving equitable STEM learning opportunities in a school. Therefore, storytelling is a means for achieving organizational resilience. Through a comparative case study design, this paper explores challenges identified by educational leaders (e.g., principals, STEM coordinators, teacher leaders, etc.) who worked with teams to activate interdisciplinary learning to support thriving STEM programming to enhance equitable science instruction. This study specifically explores why STEM leaders tell stories (purpose/ real buy-in), what stories STEM leaders tell to support their work towards equitable STEM education, and how aspects of organizational resilience are employed in STEM education organizations.